Pemberdayaan dan peningkatan kemampuan masyarakat usia sekolah melalui pendidikan tambahan berbasis media melalui KKN-PPM di Desa Lerang Kabupaten Pinrang - Fajar Arwadi; Sahlan Sidjara (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The purpose of this Community Partnership Program (PKM) activity is to provide knowledge and sewing skills with a simple pattern technique in a group of young women in Bonto Jai Village, Bissapu District, Bantaeng Regency. The provision of these skills is based on several problems in the group of teenager girl as partners in Bonto Jai Village, namely: the low level of knowledge and skills, especially sewing skills: there are no specialized institutions to provide training in the form of sewing skills; and the lack of participant fees for attending education in the form of commercial courses. To achieve the goals of the success of this Community Partnership Program the solution offered is to assist during the activity, and to apply learning methods that are easily understood by the community partnership program participants. The results of the PKM activities carried out at Bonto Jai Village were the opening of opportunities for cooperation between LP2M UNM and Partners; Increased sewing knowledge and skills; Open minded insights to be developed into more professional businesses in the sewing services business.The partner of this Community Partnership Program (PKM) was the head of the Lerang subdistrict. The problem motivating this program were (1) the lack of awareness of the importance of clean environment and education for children, (2) the lack of teachers’ knowledge in teaching which results in boring learning, (3) the lack of learnng media used by teachers in learning process, (4) most people are illiterate of Al-Qur’an, and (5) the cooperative culture in the society is faded. The objectives of this program were (1) increasing parents' insights about the importance of investment in education, (2) supporting schools in Lerang sub-district in creating clean and beatiful school environment, (3). assisting teachers in making learning media which is suitable with their lessons, (4) increasing teachers' insights about learning media tools that can be used in teaching and learning. (5) creating the culture of clean environment in the community. The expected outcomes in this activity are: learning media that can be used by teachers, good awareness of the society about the importance of clean environment and education for children.